Preventive Legislative Approaches to Child Protection in the Digital Environment: A Comparative Study of Australia, France, and Egypt - Tarek El-Sayed Mahmod Abu Okeal; Hisham Al-Kasasbeh; Hanaa Ibrahiem Abdullah; Salaheldin Ragab Fathelbab (Nusantara: Journal of Law Studies, 2026)
The rapid expansion of the digital environment has significantly increased children’s exposure to various online risks, including sexual exploitation, cyberbullying, digital extortion, and violations of privacy and image rights. This study examines the effectiveness of preventive legislative frameworks in protecting minors in the digital sphere by comparing regulatory approaches in Australia, France, and Egypt. Specifically, it aims to analyse how preventive legal models in Australia and France address digital harms affecting children and to evaluate the extent to which these models can inform legislative reform within the Egyptian legal system. The research employs a qualitative approach using descriptive–analytical and comparative legal methods, focusing on statutory provisions, regulatory mechanisms, and institutional enforcement structures across the three jurisdictions. The findings reveal that Australia and France have gradually shifted from reactive criminalisation toward a proactive preventive governance model. These frameworks impose legally binding obligations on digital platforms, including age verification systems, algorithmic accountability, enhanced content moderation, and digital literacy initiatives to strengthen child safety online. Australia prioritises strict minimum-age requirements and corporate liability mechanisms, while France adopts a dual-track model combining technological verification, parental consent, and preventive educational policies alongside criminal sanctions. In contrast, Egypt’s legal framework remains predominantly reactive, with regulatory provisions dispersed across the Child Law and the Cybercrime Law, and lacking comprehensive preventive obligations for digital platforms. This study contributes to the literature by providing an early comparative analysis of recent preventive legislative reforms (2024–2026) and by identifying structural gaps in Egypt’s digital child protection regime. It further proposes policy-oriented recommendations for developing a modernised preventive framework aligned with international standards, thereby strengthening the protection of children’s rights in an increasingly digitalised society.